Direct shear behavior in concrete materials. (October 2017) - French, R.; Maher, E.; Smith, M.; Stone, M.; Kim, J.; Krauthammer, T.
Highlights: Direct shear behavior, its hazards, and observations on previous models. Recent static and impact direct shear tests of NSC, UHPC, and UHPFRC specimens. Findings from test data analyses in both the time and frequency domains. Proposed direct shear models for NSC, UHPC, and UHPFRC structural elements. Abstract: Direct shear is a sudden and catastrophic failure mechanism in structural concrete structures under highly impulsive loads. This behavior has been studied by various investigators for more than four decades on normal strength concrete (NSC) specimens. Nevertheless, this structural behavior has not been well understood for either static nor dynamic loading domains. Moreover, this behavioral mechanism has only recently been investigated on test articles made of ultra-high performance concrete (UHPC) and ultra-high performance fiber reinforced concrete (UHPFRC) materials whose responses were very significantly different from those observed on NSC specimens. The purpose of this paper is to describe the evolution in understanding direct shear behavior in NSC, UHPC, and UHPFRC for static and dynamic loading regimes, based on data in both the time and frequency domains. The results are compared with the original and modified empirical direct shear models to highlight both the evolution in understanding direct shear behavior and to propose direct shear models for NSC, UHPC, and UHPFRC specimens under both static and impact loads.